Indonesia-North Korea Diplomatic Relations: Effort to Pursue National Interest and Create Regional Peace [Hubungan Diplomatik Indonesia – Korea Utara: Upaya Mewujudkan Kepentingan Nasional dan Menciptakan Perdamaian Regional] - Hendra Manurung (Jurnal Politica, 2020)
This article aims to analyze the implementation of Indonesia’s foreign policy towards North Korea over its approximately fifty-nine years of bilateral relations, since 17 June 1961. The arguments posited in this regard is that the implementation of Indonesia’s foreign policy towards North Korea has been counterproductive. Under the leadership of President Joko Widodo, Indonesia actually has great potential to influence North Korea’s conducts through the close diplomatic relations that the two countries have developed. The friendship between Indonesia and North Korea began since the two states conducted reciprocal official visits 1964 and 1965. Indonesia’s foreign policy towards South Korea has often been carried out to influence the offensive decisions of North Korean leaders, especially in relation to the issue of nuclear weapon development. The key question is what should and can Indonesia do next to help create peace and stability in the Korean Peninsula by adhering to the principles of a free and active foreign policy? Why is it necessary for Indonesia to do this and how can Indonesia carry out this foreign policy towards North Korea? After becoming President since 2011, Kim Jong-un had to weaken his father’s winning coalition to consolidate domestic political stability. However, North Korea’s domestic market reforms have had the effect of eroding the Kim family’s ideological appeal. This is relevant to the expansion of political influence from Pyongyang, which prioritizes the continuation of a fragile centralized authoritarian power while maintaining sustainable domestic economic growth.AbstrakArtikel ini bertujuan menjelaskan secara analitis bagaimana implementasi kebijakan luar negeri Indonesia terhadap Korea Utara selama 59 tahun sejak 17 Juni 1961. Argumen yang ingin disampaikan tentang implementasi kebijakan luar negeri Indonesia terhadap Korea Utara adalah kontraproduktif. Indonesia di bawah kepemimpinan Presiden Joko Widodo berpotensi besar untuk mampu memengaruhi perilaku Korea Utara melalui hubungan diplomatik. Persahabatan Indonesia dan Korea Utara dimulai sejak saling kunjung di 1964 dan 1965. Orientasi politik luar negeri Indonesia di masa lalu hingga saat ini, telah sering dilakukan untuk memengaruhi keputusan ofensif para pemimpin Korea Utara, khususnya terkait dengan isu pengembangan senjata nuklir. Pertanyaannya adalah apa yang harus dan sebaiknya dilakukan Indonesia selanjutnya untuk membantu menciptakan perdamaian dan stabilitas di Semenanjung Korea dengan tetap berpegang pada prinsip politik luar negeri bebas dan aktif? Mengapa hal tersebut perlu dilakukan oleh Indonesia dan bagaimana cara menjalankan kebijakan luar negeri terhadap Korea Utara tersebut? Kim Jong-un, setelah menjadi Presiden sejak 2011, harus melemahkan posisi koalisi pemenang ayahnya untuk konsolidasi stabilitas politik dalam negeri. Bagaimanapun, reformasi pasar domestik Korea Utara telah berdampak pada pengikisan daya tarik ideologis keluarga Kim. Hal ini relevan dengan perluasan pengaruh politik dari Pyongyang memprioritaskan pada keberlangsungan kekuatan otoriter terpusat yang rentan seiring bagaimana dapat mempertahankan pertumbuhan ekonomi dalam negeri berkelanjutan.